Potency of selected berries, grapes and citrus fruit as neuroprotective agents - Tan, Shih Jen; Ismail, Intan Safinar (Hindawi, 2020)
A healthy diet should nourish the brain with essential nutrients, including bioactive compounds, for normal brain functioning and to protect it from the negative effects of inflammation and oxidative stress. In this review, a concise summation of the protective effects of selected fruits, namely, berries, grapes, and citrus fruits, against neurological disorder is presented. The focus is on the neuroprotective potential of these fruits against neurodegenerative and mental disorders. The fruits selection was based on the vast reported pharmacological studies on their neuroprotection efficacies. Hence, the respective knowledge and limitations are discussed based on the biological and pharmacological evidence compiled from the previously reported laboratory, epidemiology, and intervention trials.